2018
DOI: 10.1186/s12906-018-2381-8
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical analysis and antidiabetic potential of Elaeagnus umbellata (Thunb.) in streptozotocin-induced diabetic rats: pharmacological and computational approach

Abstract: BackgroundThe fruit of Elaeagnus umbellata has high medicinal values and is an excellent source of phytochemicals. This study was aimed to evaluate the antioxidant, enzyme inhibitory and antidiabetic potential of Elaeagnus umbellata.MethodsThe antioxidant potential of the crude extract and subfractions of E. umbellata fruit were determined using DPPH (2, 20-diphenyl-1-picrylhydrazyl) and ABTS (2, 2′-azinobis-3-ethylbenzothiazoline-6-sulfonic acid) assays. The enzyme inhibitory potentials of extracts against α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
92
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 61 publications
8
92
0
2
Order By: Relevance
“…The inhibiting both α‐glucosidase and α‐amylase has reported by varied plant bioactive compounds. Nazir et al 4 report that the chloroform extract of Elaeagnus umbellata (Thunb.) has shown high inhibitory potential on both α‐glucosidase and α‐amylase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibiting both α‐glucosidase and α‐amylase has reported by varied plant bioactive compounds. Nazir et al 4 report that the chloroform extract of Elaeagnus umbellata (Thunb.) has shown high inhibitory potential on both α‐glucosidase and α‐amylase.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is the main source of staple food in the world, especially in Asia 4 . Moreover, rice has been known as the source of bioactive compounds related to improvement of human health (Ryan, 2011) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…E. angustifolia exerts antinociceptive, anti-inflammatory, antimicrobial, antioxidant, and antimutagenic activities [18,19]. E. umbellate is known to have antidiabetic, antioxidant, and anticancer properties [20,21]. Interestingly, our previous study reported the memory-ameliorating effects of E. glabra f. oxyphylla in a mouse model of scopolamine-induced memory impairment [22].…”
Section: Introductionmentioning
confidence: 97%
“…E . umbellate is known to have antidiabetic, antioxidant, and anticancer properties [ 20 , 21 ]. Interestingly, our previous study reported the memory-ameliorating effects of E .…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic drugs are often coupled with a number of secondary effects. Medicines based on natural herbs could generate fewer or no secondary effects and as a result are still attractive in human communities [4]. Nowadays, about 80% of the population throughout the world rely on traditional herbal medicine in order to meet their health care needs [5].…”
Section: Introductionmentioning
confidence: 99%